An assessment of the key determinants of energy resilience in Bangladesh - Sharmin, Farzana; Dhakal, Shobhakar; Salam, P. Abdul; Tsusaka, Takuji W.; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
Energy is recognized as the driver of economic growth and a means of ensuring inclusive and sustainable development. The importance was reaffirmed by the recent global crises: food and energy price inflation and climate crisis owing to the COVID-19 pandemic and the subsequent Russia-Ukraine war-induced supply disruptions. The energy sector was both an absorber and propagator of these crises creating a ripple effect on the overall macroeconomic stability and the cost-of-living across the world. It is critical to examine the key issues of a representative developing country's energy system resilience performance for developing appropriate policy measures. Bangladesh is one of the world{u2019}s fast-growing economies with a fossil-fuel-dependent energy system. Like many other developing countries, the energy system has low energy efficiency, poor energy diversification, high import dependence and low institutional quality. These inherent characteristics warrant a holistic understanding of energy resilience issues to support inclusive and sustainable development. The literature review confirms a significant research gap in terms of determinants of the resilience of the energy system, considering a holistic approach covering a multitude of climate and non-climate-change related disruptions. The study aimed at identifying key energy resilience issues for the energy system of Bangladesh. A "Composite Energy Resilience Index (CERI)" was developed with 15 individual indicators. A two-round Delphi technique was used to interview stakeholders to extract key energy resilience issues of Bangladesh based on a conceptual framework from the literature review. The indicators were selected from the Delphi technique's findings, and the energy resilience framework for the country was developed using these indicators. The constructed CERI indicated that the energy resilience of Bangladesh was critically dependent on affordability, sustainability and availability issues such as GDP per capita, per capita generation, import diversification, reserves in months, investment in the energy sector, self-sufficiency, energy intensity and CO2 emission reduction. These components contributed 60 to 70 per cent to the energy system resilience performance. Contrary to the perception of the Delphi respondents, the PCA findings suggest that the contribution from the qualitative issues, such as corruption, government effectiveness and regulatory qualities, was the least. Nevertheless, the qualitative aspects of energy system management also critically contributed to the energy system resilience performance. Also, key determinants of energy resilience are likely to contribute to climate change adaptation measures through energy transition and improved energy system resilience. It provides important policy implications in terms of developing holistic energy strategies for supporting the economic development aspiration of the country. The findings also suggest that the energy resilience performance under the planned scenario based on the long-term government plans, business-as-usual, and conservative scenarios is likely to improve resilience performance by 2030. However, the required improvement might be ambitious, considering the low base level and the prevailing geopolitical situation. The findings are supported by the Current Status Index, measuring the status of energy resilience performance against the target resilience performance, and the Anticipated Progress Index showing the time expected to attain the target resilience level. As such, a systematic approach to energy system resilience is warranted. The findings are critical for aspiring developing countries with similar macroeconomic and energy system setups to ensure robust energy sector policies supporting sustainable development.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Energy, School of Environment, Resources and Development
Thesis (Ph.D.) - Asian Institute of Technology, 2023
Keywords: Energy development -- Bangladesh; Renewable energy sources -- Bangladesh; Energy policy -- Bangladesh; Sustainable development -- Bangladesh